Does Listening Habit Influence Students’ Listening Comprehension on TOEFL? Focusing on University Students’ Perspectives - Faridatul Istighfaroh; Dzulfikri Dzulfikri; Indah Khoirun Nisa (UICELL, 2022)
The aim of this study is to unpack the influence of listening habits on listening skills, particularly in the TOEFL ITP test. Among three available sections in TOEFL, the focus of this study is the listening section. Little did previous research reveal the relevant effect of listening behavior on the listening assessment of the TOEFL. Since listening becomes the most complicated skill for most test takers, this research is going to outline whether there is a correlation between students’ habitual listening in the past with their listening comprehension on the TOEFL test. The methodology used in this research is quantitative research with 80 university students as participants. With the result of a significant 2-tailed number at 0.26 using Pearson Bivariate Correlation, the finding reveals that there is no correlation between listening habit and TOEFL listening comprehension from the university student’s point of view. However, the arguments by university students of this statistical result are described narratively. Keywords: TOEFL, Listening Habit, Listening Comprehension